CHINA AND QUAD 2.0: Between response and regional construct. (2nd January 2020) - Sarkar, Mrittika Guha
ABSTRACT: The existing literature on the Quadrilateral Initiative or Quad 2.0, has primarily focused on why the US, India, Japan and Australia have been promoting a strategic mechanism and how it could possibly contain an increasingly assertive China in the Indo-Pacific. However, what remains overlooked is the Chinese perception towards the Quad, which remains complex and systemic, underpinned by Beijing's national interests, national identity in the regional affairs, and a desire to attain the "Chinese Dream". While the official Chinese reaction to the "Asian NATO" has mainly been dismissive, this paper argues that Beijing's response to the Quad with its underlying apprehensions, is structurally linked to China's rise vis-à-vis India, the re-emergence of Japan in Asia and beyond, Australia's recent firm and calculated approach towards China, and US' rebuilt Asia strategy extending beyond military connotations.